Religiously-Integrated Cognitive Behavioural Therapy for Major Depression in Chronic Medical Illness: Review of Results from a Randomized Clinical Trial. (15th August 2016) - Koenig, Harold; Boucher, Nathan; O'Garo, Keisha-Gaye; Pearce, Michelle
Abstract : A randomized clinical trial was conducted over a three year period to compare the effectiveness of religiously-integrated cognitive behavioural therapy (RCBT) with conventional CBT (CCBT) for the treatment of a major depressive disorder (MDD). A total of 132 participants with chronic medical illness and MDD were enrolled in the trial (CCBT=67, RCBT=65). Ten 50-minute treatment sessions were delivered by master's level certified counsellors over 12 weeks. All sessions were delivered remotely, largely over the telephone. In this review, we describe the findings from this trial, including the effects on depressive symptoms, positive emotions, and immune and endocrine markers in blood and urine. We also examine the effects of treatment based on genotype, in particular polymorphisms of the serotonin transporter, serotonin receptor, and monoamine oxidase genes. Lessons learned from conducting this trial are also discussed. Although not designed as a non-inferiority trial, the results suggest that RCBT is as effective as standard CBT in the treatment of major depression in this setting, especially among highly religious clients, and can be delivered by appropriately trained chaplains.